The relationship between entrepreneurship and self-employment intention among undergraduate students of Universiti Utara Malaysia - Serah, Abijo Temitayo (2014)
Entrepreneurship education is constructed to instill skills, knowledge and motivation needed to understand and encourage entrepreneurial success in various settings. This would enhance necessary identification and avoid many pitfalls that awaits less trained towards being self-employed. Meanwhile, training will be appreciated though may initially be perceived as a cost in terms of time and money. Therefore, this study report the results of cross sectional research that focused on the relationship between entrepreneurship education and self-employment intentions among students of Universiti Utara Malaysia (UUM). The sample composed of 76 undergraduate students pursuing Bachelor of Entrepreneurship (B.Ent) in UUM. The collected data was analysed using SPSS 16.0 which provided descriptive statistics and regression analysis. The respondents were randomly selected. The findings of the study showed that there is significant relationship between entrepreneurship education, perceived desirability of self-employment and self-employment intentions. In contrast to the expectation, finding shows that there is negative influence between previous entrepreneurial experience and self-employment intentions. This study provides opportunity to policy makers and government to inculcate entrepreneurial programmes which would enhance individual attitudes to self-employment. Among the limitations to study are time limit and the use of self-report measure.